CUSTOMER EXPECTATIONS IN THE GERMAN BANKING SECTOR - Löffler, Lana (Journal of Economic Development, Environment and People, 2022)
The last financial market crisis, which affected the whole world in 2008, brought about major changes. As a result of this crisis, customers have become more suspicious and since then the banks have been constantly being prescribed new regulations and controls for supervision. History shows that crises repeat themselves, so that companies always had to adapt to the times and changing requirements. Due to the rapid change in the financial services offered, national borders are being overcome. The boundaries of conventional market segments are eliminated and new products are created. The challenge for the money industry is growing with new providers, like Fintechs, and products and throughout all those changes customers adapt their expectations and their satisfaction might be affected.